Compression Therapy for HIV-Associated Kaposi Sarcoma Leg Lymphedema: Results of the Kenyan Improvised Compression for Kaposi Sarcoma Randomized Controlled Trial. (13th January 2022) - Chang, Aileen Y.; Karwa, Rakhi; Odhiambo, Haji; Were, Phelix; Fletcher, Sara L.; Tonui, Edith C.; Kohn, Michael A.; Lee, Jeannette; Chang, Di; Lensing, Shelly; Namaemba, Diana Flora; Busakhala, Naftali; et al.
Abstract : PURPOSE: Evaluate the effectiveness of compression while receiving chemotherapy compared with chemotherapy alone in the treatment of HIV-associated Kaposi sarcoma (KS) lymphedema. METHODS: A randomized controlled trial was conducted in a single oncology clinic in western Kenya (NCT03404297 ). A computer-generated randomization schedule was used to allocate treatment arms. Randomized block design was used for stratification by lymphedema stage. Participants were HIV positive adults age ≥ 18 years on antiretroviral therapy with biopsy-proven KS associated with leg lymphedema and being initiated on chemotherapy. The intervention was 10 weeks of weekly clinic-based application of two-component paste compression bandages. The primary outcome was change in the Lower Extremity Lymphedema Index (LELI) score from week 0 to week 14. The secondary outcomes were change in the Lymphedema Quality of Life measure (LYMQOL) and change in the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 score from week 0 to week 14. Blinded outcome assessments were conducted. RESULTS: Of 30 participants randomly assigned, 25 eligible patients (chemotherapy [control], n = 13; compression plus chemotherapy [intervention], n = 12) returned at week 14. Change in LELI, LYMQOL, and EORTC QLQ-C30 scores between week 14 and week 0 did not significantly differ by arm. The mean (standard deviation) change in LELI score was –25.9 (34.6) for the control arm compared with –13.3 (29.5) for the intervention arm, P = .340. The difference (95% CI) in the change in LELI score was –12.6 (–39.3 to 14.1). CONCLUSION: Future studies evaluating a 14-week change in LELI for KS lymphedema should assume a standard deviation of approximately 30. Lessons learned from this pilot trial should inform the development of a larger, multicenter trial to evaluate the effectiveness of compression for KS lymphedema. Abstract :